A chattering-free fuzzy hybrid sliding mode control of an electrohydraulic active suspension. (January 2018) - Shaer, Bassel; Kenné, Jean-Pierre; Kaddissi, Claude; Fallaha, Charles
This paper introduces a new hybrid controller for position and force control of an electrohydraulic car active suspension. In most hybrid controllers, a switching function is normally used in order to take advantage of two separate controllers. Switching between the two controllers produces a chattering in the system, in addition to the chattering that may be inherent to the controller itself, which deteriorates the system performance. In this work, we resolved the switching limitations dilemma by transitioning from one controller to another through two low-pass filters. These filters are used with variable gains to improve the new hybrid position/force controller performance that we developed. The produced control signal is a structured combination, in which the signal coming from the position controller reduces the effect of road perturbations on passengers by bringing the car's vertical motion to zero. Simultaneously, the signal from the force controller tracks a reference force and thus reduces the force transmitted to passengers. To eliminate the chattering that is inherent to the sliding mode controller, we introduced an exponential reaching law function to the hybrid sliding mode controller. This exponential function also reduced the response time, consequently speeding up the system reaction to suppress perturbations. In addition to that, a recent sliding surface-based controller is applied to vary the filters' gains and obtain better performance. The frequency analysis is done to verify the controller performance. The proposed hybrid controller is also validated in real time on active suspension workbench and compared with a classical PID controller.